PENGARUH PEMBERIAN JENIS PUPUK KANDANG DANPUPUK FOSFAT TERHADAP PERTUMBUHAN DAN HASIL JAGUNG HIBRIDA (Zea mays L) - Sukarti, Sukarti; Jaenudin, Amran; Efendi, Ali (Agroswagati : Jurnal Agronomi, 2021)
The objectives of this study were: (1) to determine the effect of manure and phosphate fertilizers on the growth and yield of hybrid maize; (2) to identify the type of manure and dosage of phosphate fertilizer that produced the best growth and yield; and (3) to analyze the correlation between growth components and yield. The research was conducted using an experimental method with a randomized block design consisting of 12 combinations of manure and phosphate fertilizer treatments, each replicated three times, resulting in 36 experimental plots. The results showed that: (1) application of manure and phosphate fertilizers significantly affected plant height, leaf number, leaf area index, stem diameter, root volume, ear length, ear diameter, ear weight without husks per plant and per plot, number of seeds per ear, 100-seed weight, and dry seed weight per plant and per plot, but had no significant effect on relative growth rate and number of cobs per plot; (2) the treatment of 10 t/ha of chicken manure combined with 150 kg/ha of phosphate fertilizer produced the highest dry seed yield of 6.05 kg per plot (equivalent to 10.08 t/ha), which was not significantly different from treatments with sheep manure or cow manure at 10 t/ha combined with 150 kg/ha phosphate fertilizer, or with chicken, sheep, or cow manure at 10 t/ha combined with 100 kg/ha phosphate fertilizer; and (3) there was a significant positive correlation between plant height, leaf number, leaf area index, stem diameter and dry seed weight per plot, while root volume and relative growth rate showed an insignificant positive correlation with yield.